Perceived Pathways of Change in an Interpersonal Violence Intervention for Mothers: The Importance of Self-Compassion - Kirsten MacAulay; Naomi C. Z. Andrews; Mary Motz; Gloria J. Lee; Debra J. Pepler (Behavioral Sciences, 2025)
Interventions to support mothers experiencing interpersonal violence are critical, yet most evaluation research focuses on outcome evaluation, rather than understanding the pathways of change. The goal of the current study was to understand, via mothers’ own perspectives, the specific key pathways through which participation in an interpersonal violence intervention resulted in perceptions of change for mothers and their children. The participants (N = 43, 18–43 years old) were mothers who attended and completed a 6–8-week interpersonal violence intervention within 11 community organizations across Canada. Approximately 1–2 months following the intervention, participants completed semi-structured interviews or focus groups wherein they were asked open-ended questions about their experiences in the intervention. Using a phenomenological approach, the results indicated that (1) mothers were able to identify changes in their cognitions and behaviors across three key domains (self, relationships, and parenting), (2) mothers linked these changes to their experiences in the intervention. We integrated and mapped the perceived pathways of change experienced by mothers, which included critical pathways involving self-compassion and self-forgiveness leading to self-esteem and empowerment. The results have implications for our ability to effectively deliver this interpersonal violence intervention, as well as more broadly to improve our understanding of the pathways of change for mothers experiencing violence in relationships.